Prevalensi nyeri bahu pada peserta klub kebugaran - F.X Juanda Setiajaya (Intisari Sains Medis, 2022)
Background: Shoulder pain is pain that arises in the shoulder area caused by structural disorders of the shoulder such as muscles, bones, ligaments or tendons. Shoulder pain is often made worse by exercise. Nowadays many people join fitness clubs to exercise, one of the exercises is lifting weights. Certain movements, such as the bench press, pectoral fly, and overhead press, are weight-bearing exercises that put a lot of weight on the shoulders and can cause shoulder pain. Factors of age, gender and level of physical activity also play a role in the occurrence of shoulder pain in a person. This study was conducted to determine the prevalence of shoulder pain in fitness club participants and to describe the influencing factors. Methods: This study is a cross-sectional survey from July to September 2016. The respondents in this study were the fitness club participants at the Golf Graha Family and Country Club, Surabaya as many as 73 people using purposive sampling technique. The variables in this study consisted of gender, age, level of physical activity, exercise patterns, and shoulder pain. The data obtained will be presented descriptively. Results: There were 73 samples involved in this study. The mean age was 28.48±10.362, of which 53.4% ​​were in the 17-25 year old group. Female gender, age group 17-25 years, weight training pattern, and moderate activity were found to have the highest percentage of shoulder pain. Conclusion: In this study, respondents who performed weightlifting exercises that supported the shoulders were also more prone to experiencing shoulder pain.   Latar belakang: Nyeri bahu adalah rasa sakit yang timbul pada daerah bahu disebabkan oleh gangguan struktur bahu seperti otot, tulang, ligamen atau tendon. Nyeri bahu sering diperburuk oleh olahraga. Saat ini banyak orang yang mengikuti klub kebugaran untuk berolahraga, salah satu latihannya adalah angkat beban. Gerakan tertentu seperti bench press, pectoral fly, dan overhead press merupakan latihan angkat beban yang memberi tumpuan yang berat pada bahu dan berisiko menimbulkan nyeri bahu. Faktor usia, jenis kelamin dan tingkat aktifitas fisik juga berperan dalam terjadinya nyeri bahu pada seseorang. Penelitian ini dilakukan untuk mengetahui prevalensi nyeri bahu pada peserta klub kebugaran serta menggambarkan faktor yang berpengaruh. Metode: Penelitian ini merupakan penelitian survei potong lintang pada bulan Juli hingga September 2016. Responden pada penelitian ini adalah peserta klub kebugaran di Golf Graha Family and Country Club, Surabaya sebanyak 73 orang dengan teknik purposive sampling. Variabel dalam penelitian ini terdiri dari jenis kelamin, usia, tingkat aktivitas fisik, pola latihan, dan nyeri bahu. Data yang didapat akan disajikan secara deskriptif. Hasil: Terdapat 73 sampel yang terlibat dalam penelitian ini. Rata-rata usia 28,48±10,362 dimana 53,4% dalam rentang kelompok 17 – 25 tahun. Jenis kelamin perempuan, kelompok usia 17 – 25 tahun, pola latihan angkat beban, dan aktivitas sedang ditemukan memiliki persentase nyeri bahu tertinggi. Kesimpulan: Pada penelitian ini responden yang melakukan latihan angkat beban yang memberi tumpuhan pada bahu juga lebih rentan untuk mengalami nyeri bahu.